Development of English Curriculum Design For Active Learning: A Step-by-Step Guide to Creating Engaging and Effective Learning Experiences - Putri, Shinta Aulia; Mufaila, Selfi; Pradana, Dian Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The theory of “English curriculum design development for active learning” centers on an imaginative approach to planning English education modules that promote active learning strategies. The paper analyzes the standards and procedures included in the creation of educational modules that empower student engagement, grounded consideration, and collaborative exercises. The paper highlights the importance of matching instructional objectives with intelligent educational strategies, which ensure that learners are not passive recipients of information, but rather make students more active in English language learning. Through a blend of hypothetical systems and sensible applications, the contemplation diagram hones in on the best abilities for teachers who wish to implement viable dynamic learning methodologies in their English dialect classrooms. The suggestions of this educational module plan for enhancing dialect proficiency and fostering an energetic learning environment are thoroughly examined, emphasizing the part of flexibility and student-centered instructional methods in modern instruction. The theory of “English curriculum design development for active learning” centers on an imaginative approach to planning English education modules that promote active learning strategies. The paper analyzes the standards and procedures included in the creation of educational modules that empower student engagement, grounded consideration, and collaborative exercises. The paper highlights the importance of matching instructional objectives with intelligent educational strategies, which ensure that learners are not passive recipients of information, but rather make students more active in English language learning. Through a blend of hypothetical systems and sensible applications, the contemplation diagram hones in on the best abilities for teachers who wish to implement viable dynamic learning methodologies in their English dialect classrooms. The suggestions of this educational module plan for enhancing dialect proficiency and fostering an energetic learning environment are thoroughly examined, emphasizing the part of flexibility and student-centered instructional methods in modern instruction. Keywords English Curriculum Design, English, Active Learning, Educational Moduls.